Influence of the facility caseload on the subsequent survival of men with localized prostate cancer undergoing radical prostatectomy. Issue 21 (9th August 2019) - Barzi, Afsaneh; Lara, Primo N.; Tsao‐Wei, Denice; Yang, Dongyun; Gill, Inderbir S.; Daneshmand, Siamak; Klein, Eric A.; Pinski, Jacek K.; Penson, David F.; Quinn, David I.; Sadeghi, Sarmad
Abstract : Background: Several studies have investigated the relationship between experience measured by caseload and oncological outcomes, economics, and access to care for prostate cancer care. Oncological outcomes have been limited to biochemical failure after radical prostatectomy. Questions remain regarding the more definitive measures of outcomes and their relationship with caseload. Methods: The National Cancer Database was used to investigate the outcomes of radical prostatectomy in the United States. With overall survival (OS) as the primary outcome, the relationship between the facility annual caseload (FAC) for all prostate cancer encounters and the facility annual surgical caseload (FASC) for those requiring radical prostatectomy was examined with a Cox proportional hazards model. Four volume groups were defined by caseload: <50th percentile (volume group 1 [VG1]), 50th to 74th percentiles (volume group 2 [VG2]), 75th to 89th percentiles (volume group 3 [VG3]), and ≥90th percentile (volume group 4 [VG4]). By FAC/FASC, 11%/8%, 17%/18%, 25%/26%, and 47%/49% of patients were treated in VG1 through VG4, respectively. Results: Between 2004 and 2014, 488, 389 patients underwent radical prostatectomy. At a median follow‐up of 60.75 months, the median OS was not reached. There was a significant OS benefit as the caseload increased. For FAC, the adjusted OS difference between VG1 and VG4 at 90th percentile survivorship reached 13.2 months (hazard ratio [HR], 1.30; 95% CI, 1.23‐1.36; P  < .0001). For FASC, this was 11.3 months (HR, 1.25; 95% CI, 1.192‐1.321; P  < .0001). Conclusions: There is a statistically significant OS advantage from performing radical prostatectomy at a facility with a high annual caseload. Caseload measured by all prostate cancer encounters is a better predictor of favorable outcomes than the number of surgeries performed at a facility. Lay Summary: An in‐depth analysis of 488, 389 cases of radical prostatectomy performed in more than 1000 facilities over a 10‐year period showed better survival when surgery was performed in facilities with more experience and greater caseload. A survival difference of up to 13 months was observed when comparing patients treated at less experienced versus more experienced centers.   Experience across all stages of prostate cancer was a stronger predictor of survival outcome than just the number of surgeries performed. Abstract : There is a statistically significant overall survival advantage to performing radical prostatectomy at facilities with a high annual caseload. Caseload measured by all prostate cancer encounters is a better predictor of favorable outcomes than the number of surgeries performed at a facility.